Diagnostic reasoning in neurogenetics: a general approach - Helena Fussiger; José Luiz Pedroso; Jonas Alex Morales Saute (Arquivos de Neuro-Psiquiatria)
Establishing the definitive diagnosis of a neurogenetic disease is usually a complex task. However, like any type of clinical diagnostic reasoning, an organized process of development and consideration of diagnostic hypotheses may guide neurologists and medical geneticists to solve this difficult task. The aim of the present review is to propose a general method for diagnostic reasoning in neurogenetics, with the definition of the main neurological syndrome and its associated topographical diagnosis, followed by the identification of major and secondary neurological syndromes, extraneurological findings, and inheritance pattern. We also discuss general rules and knowledge requirements of the ordering physician to request genetic testing and information on how to interpret genetic variants in a genetic report. By guiding the requests for genetic testing according to an organized model of diagnostic reasoning and with the availability of specific treatments, clinicians may find greater resoluteness and efficacy in the diagnostic investigation, shortening the struggle of patients for a definitive diagnosis.